O homossexual respeitável: elaborações, impasses e modos de uma experiência subjetiva - Assis, Eduardo Moreira (2011)
This Research claims to lie on the field of LGBTQ studies and analyses the possibility of homosexual existence having as a site of studies a small town in South Minas Gerais. From the life experience of men between 21 and 50 years old, self nominated homosexual, it is approached the homosexual subjective constitution and the experience of the respectable homosexual meaning the respectable homosexual as a set of practices, representation and values shared by the individuals. The apprehension of the normal homosexual social phenomenon is observed in three views. At the first one itʼs observed the relation between homosexuality and a small town context exploring the urgent existence possibilities. After that itʼs considered the homosexual subject processes under the modern sexuality mechanism and homophobia. Finally itʼs approached the ways of existence for the respectable homosexual considering the homosexual subjective under negotiation in a small urban context